Century-long record of black carbon in an ice core from the Eastern Pamirs: Estimated contributions from biomass burning. (August 2015) - Wang, Mo; Xu, Baiqing; Kaspari, Susan D.; Gleixner, Gerd; Schwab, Valérie F.; Zhao, Huabiao; Wang, Hailong; Yao, Ping
Abstract: We analyzed refractory black carbon (rBC) in an ice core spanning 1875–2000 AD from Mt. Muztagh Ata, the Eastern Pamirs, using a Single Particle Soot Photometer (SP2). Additionally a pre-existing levoglucosan record from the same ice core was used to differentiate rBC that originated from open fires, energy-related combustion of biomass, and fossil fuel combustion. Mean rBC concentrations increased four-fold since the mid-1970s and reached maximum values at end of the 1980s. The observed decrease of the rBC concentrations during the 1990s was likely driven by the economic recession of former USSR countries in Central Asia. Levoglucosan concentrations showed a similar temporal trend to rBC concentrations, exhibiting a large increase around 1980 AD followed by a decrease in the 1990s that was likely due to a decrease in energy-related biomass combustion. The time evolution of levoglucosan/rBC ratios indicated stronger emissions from open fires during the 1940s–1950s, while the increase in rBC during the 1980s–1990s was caused from an increase in energy-related combustion of biomass and fossil fuels. Highlights: rBC concentration in an ice core spanning 1875–2000 AD was retrieved. rBC concentration was 4 times higher in the mid-1970s to 2000 AD than before. Levoglucosan/rBC ratio indicates increased open-fires in the 1940s–1950s. Anthropogenic emissions in the 1980s–1990s contributed more to rBC deposition.